Splintering urbanism : networked infrastructures, technological mobilities and the urban condition - Graham, Stephen, 1965-; Marvin, Simon, 1963- (London ; New York : Routledge, 2001)
This text offers an international and interdisciplinary analysis of the complex interactions between infrastructure networks and urban spaces. Drawing on case studies and examples from across the globe, it offers a statement on the urban condition.
1. Introduction -- Pt. 1. Understanding splintering urbanism. 2. Constructing the modern networked city, 1850-1960 -- 3. The collapse of the integrated ideal -- 4. Practices of splintering urbanism -- 5. The city as sociotechnical process -- Pt. 2. Exploring the splintering metropolis. 6. Social landscapes of splintering urbanism -- 7. "Glocal" infrastructure and the splintering of urban economies -- Pt. 3. Placing splintering urbanism. 8. Conclusion.
Includes bibliographical references (pages 432-462) and index.
ARC
Department of Architecture
Keywords: Cities and towns; Infrastructure (Economics) -- Computer networks; Technology -- Social aspects; Globalization; Information society